Estimating technical and irrigation water productivities in rice production in Tamil Nadu, India - Kuppannan, Palanisami; Ramarao, R.C.; Samiappan, S.; Malik, Ravinder Paul Singh (Wiley, 2017)
The overall measure of farm-level technical efficiency is generally used to derive recommendations for the use of individual inputs. In this paper, joint estimation is made of technical and individual input-use (e.g. irrigation water productivity) efficiencies. This indicates that overall technical efficiency is not an indication of the efficiency level of all the individual inputs used. This is because the efficiency of individual inputs may vary and suggests that greater effort should be made to improve such efficiencies in comparison with overall technical efficiency. The model is applied to rice production in four tank-irrigated districts in Tamil Nadu, India, which is one of the most important tank-irrigated areas in India. The average technical efficiency is 62.8%, which indicates that in order to achieve the present level of production, 62.8% of the current level of input resources is sufficient. Average irrigation water productivity is estimated at ~34%, indicating that current output levels could be achieved with 66% less irrigation water. These findings also suggest the need for improvements in crop and water productivity. Thus, the paper makes a contribution in the form of a methodology development for possible adoption in future irrigation water productivity studies.